INTERACTIVE AND DIGITAL METHODS IN TEACHING ACADEMIC ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The landscape of academic English instruction is continuously evolving, shaped by technological advancement and changes in pedagogical philosophy. As educational technology becomes ubiquitous and student demographics grow increasingly diverse, the adoption of interactive and digital methods has emerged as a cornerstone of modern academic English education. These innovations not only enrich the learning experience but also address the specific needs of students striving to master academic language skills in an ever-globalizing world. This article examines the theoretical underpinning, practical applications, transformative impact, and future potential of interactive and digital teaching methods in academic English, offering educators insights to enhance effectiveness and student engagement.
Keywords: Academic English, digital pedagogy, interactive methods, blended learning, communicative competence, gamification, educational technology, formative assessment, multimedia literacy, open educational resources.